2018
DOI: 10.1158/1541-7786.mcr-18-0269
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1-Interacting Protein OLA1 Requires Interaction with BARD1 to Regulate Centrosome Number

Abstract: BRCA1 functions as a tumor suppressor in DNA repair and centrosome regulation. Previously, Obg-like ATPase 1 (OLA1) was shown to interact with BARD1, a heterodimer partner of BRCA1. OLA1 binds to BRCA1, BARD1, and γ-tubulin and functions in centrosome regulation. This study determined that overexpression of wild-type OLA1 (OLA1-WT) caused centrosome amplification due to centriole overduplication in mammary tissue-derived cells. Centrosome amplification induced by overexpression of the cancer-derived OLA1 mutan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Literature data report that FL BARD1 not in complex with BRCA1 acts as an adaptor for p53, enabling it to be targeted for ATM/ATR-directed serine-15 phosphorylation (p53Ser-15) following IR/ UV-induced DNA damage in several cell types. This phosphorylation is required for p53 apoptotic function (25,26). We observed that the depletion of FL BARD1 (in shBARD1 cells) disrupted p53Ser-15 in post-IR SKNSH and SHSY5Y cells whereas p53Ser-15 was observed in post-IR SKNSH and SHSY5Y shCTR cells ( Figure 4A).…”
Section: Fl Bard1 Functions In Regulating G2/m Cell Cycle Phase and Amentioning
confidence: 85%
See 1 more Smart Citation
“…Literature data report that FL BARD1 not in complex with BRCA1 acts as an adaptor for p53, enabling it to be targeted for ATM/ATR-directed serine-15 phosphorylation (p53Ser-15) following IR/ UV-induced DNA damage in several cell types. This phosphorylation is required for p53 apoptotic function (25,26). We observed that the depletion of FL BARD1 (in shBARD1 cells) disrupted p53Ser-15 in post-IR SKNSH and SHSY5Y cells whereas p53Ser-15 was observed in post-IR SKNSH and SHSY5Y shCTR cells ( Figure 4A).…”
Section: Fl Bard1 Functions In Regulating G2/m Cell Cycle Phase and Amentioning
confidence: 85%
“…The BARD1 RING domain is an ubiquitin ligase forming a heterodimer with BRCA1, which also harbors a RING domain. The heterodimeric complex localizes at site of DNA damage and functions in the regulation of centrosome amplification and chromosome de-condensation (25,26). Literature data report that BARD1 and BRCA1 gene knockouts have similar phenotypes demonstrating that both BARD1 and BRCA1 are essential for cell viability and maintenance of genome integrity (27,28).…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…BRCA1/BARD1 monoubiquitinates γ-tubulin at lysines K48 and K344, and the C-terminal region of BRCA1 is required for this function [10]. Suppression or overexpression of BRCA1 or BARD1 results in centrosome amplification in mammary tissue-derived cells [10,47]. Centrosome amplification induced by BRCA1 suppression is caused by premature centriole disengagement and centriole reduplication [48].…”
Section: The Brca1/bard1 Heterodimer Functions In Centrosome Regulationmentioning
confidence: 99%
“…OLA1 can directly interact with BRCA1 and γ-tubulin by bounding to the amino-terminal of these two proteins, and this interaction is very important for the centrosomal regulation (Matsuzawa et al, 2014). And knockdown of OLA1 results in the centrosome amplification of centrosome and the disorders in microtubule aster formation (Matsuzawa et al, 2014;Yoshino et al, 2018). It is noteworthy that, BRCA1 has been shown to exert functions in oocyte meiosis, and knockdown of BRCA1 in mouse oocyte causes abnormal spindle assembly and the dysfunction of SAC (Xiong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%